2014
DOI: 10.3748/wjg.v20.i47.18013
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the efficacy of probiotics inHelicobacter pylorieradication therapy

Abstract: AIM:To evaluate the role of probiotics in the standard triple Helicobacter pylori therapy. METHODS:In this meta-analysis, we investigated the efficacy of probiotics in a standard triple H. pylori therapy in adults. Searches were mainly conducted in MEDLINE/PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials. Fourteen studies met our criteria, and the quality of these studies was assessed using the Jadad scale. We used STATA version 12.0 to extract data and to calculate the odds ratios (ORs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 37 publications
6
47
2
12
Order By: Relevance
“…In a study by Lv et al [127] , the cure rates in the probiotic supplementation group were superior to those in the group that did not receive probiotics (RR, 1.12; 95%CI: 1.06-1.19), and probiotics reduced the risk of H. pylori therapy related side effects (RR, 0.60; 95%CI: 0.40-0.91). In another meta-analysis, the pooled odd ratios (ORs) for the eradication rate were higher in the probiotic group than the control group (OR = 1.67; 95%CI: 1.38-2.02) by ITT, and adverse effects were lower in the probiotic group (OR = 0.49, 95%CI: 0.26-0.94) [128] . This study also showed racial differences in the sensitivity to probiotics, with greater differences in Asian populations compared to Caucasians.…”
Section: Probiotics As Another Approach To Improve Eradication Ratesmentioning
confidence: 99%
“…In a study by Lv et al [127] , the cure rates in the probiotic supplementation group were superior to those in the group that did not receive probiotics (RR, 1.12; 95%CI: 1.06-1.19), and probiotics reduced the risk of H. pylori therapy related side effects (RR, 0.60; 95%CI: 0.40-0.91). In another meta-analysis, the pooled odd ratios (ORs) for the eradication rate were higher in the probiotic group than the control group (OR = 1.67; 95%CI: 1.38-2.02) by ITT, and adverse effects were lower in the probiotic group (OR = 0.49, 95%CI: 0.26-0.94) [128] . This study also showed racial differences in the sensitivity to probiotics, with greater differences in Asian populations compared to Caucasians.…”
Section: Probiotics As Another Approach To Improve Eradication Ratesmentioning
confidence: 99%
“…70,71 Now 10 meta-analyses have been published addressing the specific benefit of Lactobacillus and Bifidobacterium, 72,73 bovine lactoferrin, 74,75 fermented milk-based, 76 Lactobacillus, 77,78 and Saccharomyces boulardii 79 probiotic formulations as well as probiotics as a whole therapeutic group. [80][81][82] Available evidence collectively points toward a benefit of using probiotic for decreasing antibioticrelated side effects and, to a much lesser extent, increasing cure rates.…”
Section: Probioticsmentioning
confidence: 98%
“…10 Although primary intervention strategies basically rely on efforts to eradicate the bacteria, the best approach to eradication therapy has been, and continues to be, under debate (also in view of the emergence of antibiotic-resistant H pylori strains). [11][12][13][14][15][16] GASTRIC CANCER RISK: THE ASSESSMENT GC risk can be assessed using both noninvasive and invasive methods.…”
Section: Gastric Cancer Risk: Epidemiologic Trendsmentioning
confidence: 99%